Stigma, discrimination and the implications for people living with HIV/AIDS in South Africa - Donald Skinner; Sakhumzi Mfecane (Taylor & Francis Group, 2004)
Stigma and discrimination play significant roles in the development and maintenance of the HIV epidemic. It is well documented that people living with HIV and AIDS experience stigma and discrimination on an ongoing basis. This impact goes beyond individuals infected with HIV to reach broadly into society, both disrupting the functioning of communities and complicating prevention and treatment of HIV. This paper reviews the available scientific literature on HIV/AIDS and stigma in South Africa, as well as press reports on the same subject over a period of 3 years. Analysis of this material indicates that stigma drives HIV out of the public sight, so reducing the pressure for behaviour change. Stigma also introduces a desire not to know one's own status, thus delaying testing and accessing treatment. At an individual level stigma undermines the person's identity and capacity to cope with the disease. Fear of discrimination limits the possibility of disclosure even to potential important sources of support such as family and friends. Finally, stigma impacts on behaviour change as it limits the possibility of using certain safer sexual practices. Behaviour such as wanting to use condoms could be seen as a marker of HIV, leading to rejection and stigma. All interventions need to address stigma as part of their focus. However, the difficulty of the task should not be underestimated, as has been shown by the persistence of discrimination based on factors such as race, gender and sexual orientation.